PENGARUH MUTUAL RECOGNITION ARRANGEMENT TERHADAP PENYEBARAN TENAGA KERJA INDONESIA DIBIDANG PROFESIONAL PARIWISATA DI ERA MASYARAKAT EKONOMI ASEAN TAHUN 2015-2017 - Bela Safira; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Mutual Recognition Arrangement (MRA) is one of the important elements in the mobilization of Professional workforce in the ASEAN region, including the Tourism Professional MRA which is a driving force in improving Tourism standards and improving the qualifications of Tourism workforce in the ASEAN region. The implementation of AEC in 2015 makes ASEAN member countries have to prepare the quantity and quality of the Tourism Professional workforce.            The author uses a Liberal Institutionalist perspective to describe ASEAN as a regional institution that guides member countries in implementing free markets in order to improve the regional economy. Currently, the liberalization of professional workforce, especially in the field of tourism professionals, has become involved in multilateral trade in seeking conformity with standards, especially in the field of tourism.            This is important for the Indonesian Tourism Professional workforce in improving human resources. The Indonesian workforce, which is still dominated by a relatively low level of workforce education, indicates the need for increased certification to be able to improve the quality of the workforce in this sector and be able to continue to lead in the number of workers as well. Keywords: ASEAN, MEA, Free Market, Tourism Employment, MRA, Certification